Efektivitas Kolaborasi Model Experiential Learning Dengan Artificial Intelligence (AI) Sebagai Upaya Peningkatan Menulis Syair Siswa Kelas VII - Siti Nuraini; Cut Nuraini; Sutri Sutri (Universitas Muhammadiyah Surabaya, 2026)
This study aims to examine the effectiveness of the collaboration between the Experiential Learning model and Artificial Intelligence (AI) technology in improving the ability of eighth-grade students at SMP Tunas Darma to write traditional poems (syair). The research employed a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. Instruments used included pretest and posttest, supported by observation and documentation. The analysis results revealed a significant difference between the experimental and control groups, with a t-test significance value of < 0.001. The average N-Gain score in the experimental class was 0.7774, which falls into the high category, indicating that the collaborative implementation of Experiential Learning and AI effectively enhanced students' ability to write syair. The findings also suggest that this learning model improves student engagement, creativity, and interest in traditional literature. Keywords: learning model; experiential learning; artificial intelligence; writing; poetry